Hydrogen Sulfide Antagonizes Chronic Restraint Stress-Induced Depressive-Like Behaviors via Upregulation of Adiponectin - Tian, Qing; Chen, Lei; Luo, Bang; Wang, Ai-Ping; Zou, Wei; You, Yong; Zhang, Ping; Tang, Xiao-Qing (Frontiers in Psychiatry, 2018)
Backgroud: Chronic restraint stress (CRS) induces depressive-like behaviors in rodents, which involves dysregulation of hippocampal synapse formation and excessive autophagy. Adiponectin has antidepressant activity. Hydrogen sulfide (H2S) is a novel gasotransmitter. The present work was to investigate whether H2S antagonizes CRS-induced depressive-like behaviors in rats and to explore whether its potential mechanism involves ameliorated synaptic and autophagic dysregulation by upregulation of adiponectin. Methods: Depressive-like behavior was analyzed by the tail suspension test (TST), novelty suppressed feeding test (NSFT), and open field test (OFT). The structure of autophagy was observed under transmission electron microscopy. The expressions of adiponectin, beclin1, and sequestosome 1 (p62/SQSTMI) protein in hippocampus were measured by Western blot. The levels of synapsin1 (SYN1) in the hippocampus were calculated by Western blot and immunofluorescence technique. Results: The behavior experiments, including TST, NSFT, and OFT, showed that NaHS (a donor of H2S) reduced CRS-induced depressive-like behaviors. NaHS decreased the loss of hippocampal synapse as evidenced by increased the level of SYN1 in the hippocampus of CRS-exposed rats. NaHS rescued CRS-induced excessive hippocampal autophagy as evidenced by declines in the number of autophagosomes and the expression of beclin1 as well as increase in the expression of P62 in the hippocampus of CRS-exposed rats. NaHS upregulated hippocampal adiponectin expression in the CRS-exposed rats. Furthermore, neutralizing adiponectin by Anti-acrp30 reversed the protective response of NaHS to CRS-produced depressive-like behaviors as well as hippocampal synaptic disruption and excessive autophagy. Conclusion: H2S mitigates CRS-induced depressive behavior via upregulation of adiponectin, which in turn results in amelioration in hippocampal synapse formation dysfunction and excessive autophagy.